Answer:
Step-by-step explanation:
You can multiply the numerator and denominator by 2
(4.5/5.5)(2/2)=9/11
Answer:
(1,0)
Step-by-step explanation:
3x + 6y = 3
7x + 3y = 7
Multiply the second equation by -2
-2( 7x + 3y = 7)
-14x -6y = -14
Add this to the first equation to eliminate y
3x + 6y = 3
-14x -6y = -14
--------------------
-11 x = -11
Divide by -11
x = 1
Now find y
3x + 6y = 3
3 +6y = 3
Subtract 3 from each side
6y = 0
y =0
Answer:
B, E, D, and C
Step-by-step explanation:
Answer:
Ok for one im sooo sooorrry i know how it feels but guess what that guy is probably a loser you should tell yourself your better than him and you deserve better. Some People are just du.mb but u can do better.
Answer:
The second company is a better deal
Step-by-step explanation: